Macauba palm cake as additive in elephant grass silage (Acta Scientiarum. Animal Sciences, 2020)
The aim of this study was to evaluate the addition of macauba palm cake (Acrocomia aculeata) on the chemical composition, fermentation and aerobic stability of elephant grass silages (Pennisetum purpureum). The experiment was performed in a completely randomized design with four replicates. The treatments were composed of six levels of macauba palm cake (0, 6, 12, 18, 24, 30%) as additive to elephant grass silage. Dry matter and ethereal extract content of the silage increased linearly with the inclusion of the additive. Addition levels of 15.54% would provide 35% of dry mass, and the limit of 7.00% of ethereal extract in the silage could be obtained with 10.47%. The neutral detergent fiber content reduced linearly from 68.97 to 52.59%, but lignin increased linearly from 6.56 to 7.70%. There was a reduction of 0.17% in the ammoniacal nitrogen content for each 1% of cake. The minimum value of dry matter losses (1.33%) was estimated to the inclusion level of 23.70%. The aerobic stability increased with inclusions between 18 and 24% of cake. The use of levels between 10 and 15% of macauba palm cake are sufficient to optimize dry matter and ethereal extract contents of the silages and to provide a high aerobic stability with minimum losses.